Risk factors for hypertensive crisis in children with acute glomerulonephritis - Sherly Yuniarchan; Risky Vitria Prasetyo; Ninik Asmaningsih Soemyarso; Mohammad Sjaifullah Noer (Paediatrica Indonesiana, 2016)
Background Hypertensive crisis occurs in 1-4% of the hypertensive pediatric population, mostly due to acute glomerulonephritis (AGN). Some factors have been suggested to affect blood pressure (BP) in children, such as age, sex, race/ethnicity, obesity, and socioeconomic status, but little is known for risk factors for hypertensive crisis in AGN.Objective To analyze the risk factors for hypertensive crisis in children with AGN.Methods Retrospectively, we studied possible risk factors for hypertensive crisis in children with AGN at Dr. Soetomo Hospital from 2007 to 2011. Hypertensive crisis was defined as systolic BP ≥180 mmHg or diastolic BP ≥120 mmHg (for children ≥ 6 years of age); and systolic and/or diastolic BP >50% above the 95th percentile (for children aged <6 years). We evaluated the demographic and clinical characteristics as potential risk factors. Statistical analysis was done with Chi-square, Fisher’s exact, and logistic regression tests. Variables with P <0.25 in the univariable analysis were further analyzed by the multivariable logistic regression model. A P value of < 0.05 was considered statistically significant.Results There were 101 children included (mean age 9.7 (SD 2.17) years), with a male-to-female ratio of 2.7:1. Hypertensive crisis occurred in 42 (41.6%) children, of whom 8 had hypertensive urgency and 34 had hypertensive emergency. Proteinuria was seen in 53 children with AGN (52.5%) and was the significant risk factor for hypertensive crisis in our subjects (OR=2.75; 95%CI 1.16 to 6.52; P=0.021). Gender, clinical profiles, ethnicity, nutritional status, blood urea nitrogen (BUN), and glomerular filtration rate (GFR) were not significant risk factors for hypertensive crisis.Conclusion Proteinuria is the significant risk factor for hypertensive crisis in children with AGN.